Assessing the consistency of the implementation of the Namibian Horticultural Market Share Promotion Scheme under the General Agreement on Tariffs and Trade 1994 - Uusiku, Frans N (GSB: Faculty, 2016)
The application of Non-Tariff Measures (NTMs) and specifically non-automatic import licensing schemes has been a source of intense debate to date, despite prohibitive provisions enshrined in multilateral trade agreements. The main aim of this case study research was to assess the consistency of the implementation of the Namibian Horticultural Market Share Promotion Scheme (MSPS) under the General Agreement on Tariffs and Trade (GATT) 1994 and the World Trade Organisation (WTO). The second segment of this study looked at identifying problems associated with the implementation of the scheme, and proposed policy recommendations that are responsive to competitive challenges facing industries in the 21st century. The study used a triangulation research methodology and a rating scale was used to conduct the assessment with respect to all the applicable provisions covered in the WTO Agreement on Import Licensing Procedures. A reliability test was conducted using the SPSS statistical software in order to measure the credibility of the data (scores). In this regard, the Cronbach's alpha coefficient was very instrumental in measuring the degree of data consistency. Moreover, the relative frequency distribution was used to analyse the quantitative data, while an Interrelationship Diagram was used to analyse qualitative data.